A survey on physical factors and compressed breast thickness in voluntary mammography screening using FFDM system in Malaysia: preliminary results - Jamal, Noriah; Samad Cheung, Humairah; Che Mohamed, Siti Kamariah; Muhammed Nordin, Ellyda (Malaysian Nuclear Agency, 2013)
This paper aims at presenting preliminary results of a survey on physical factors, namely tube potential (kV), tube current exposure time product (mAs) and compressed breast thickness (CBT) during voluntary mammography screening using Full-Field Digital Mammography (FFDM) System in Malaysia. Retrospective data were collected from 1128 FFDM images of 282 women from three major ethnic groups (Malay, Chinese and Indian) who underwent voluntary screening mammography at Breast Centre, International Islamic University Malaysia from January to March 2008. Results from the present study were then compared with results from the previous study on Screen-Film Mammography System (SFM) according to the ethnic group for both Cranio-caudal (CC) and Mediol-Lateral (MLO) views. We found that the mean kV for CC view for the three ethnic groups are Malay (28), Chinese (28) and Indian (28), and for MLO view are Malay (29), Chinese (28) and Indian (29). These values are higher than the kV for SFM which were Malay (26), Chinese (27) and Indian (26) for CC and Malay (26), Chinese (27) and Indian (26) for CC and MLO views respectively. The mean mAs for CC and MLO views for FFDM were lower compared to SFM systems. These values were Malay (104), Chinese (108) and Indian (91) for CC views and Malay (106), Chinese (105), and Indian (94) for MLO views for the FFDM system. The values for SFM system are for CC and MLO views were Malay (120), Chinese (106) and Indian (126), and Malay (166), Chinese (132), Indian (183) respectively. The median CBT for CC and MLO views increased by 27% and 7% respectively on the FFDM compared to the SFM system. In conclusion, the FFDM operates with higher kV, lower mAs, and higher CBT when compared with SFM system. Median CBT on CC and MLO view with FFDM system are 27% and 7% higher respectively compared to the SFM. We are currently collecting data on mean glandular dose with FFDM systems to assess how the change in local mammography practice influences this value. This will allow comparison with related data from other parts of the world.